Discovery of ianthelliformisamines D–G from the sponge Suberea ianthelliformis and the total synthesis of ianthelliformisamine D - Sasha Hayes; Yaoying Lu; Bernd H. A. Rehm; Rohan A. Davis (Beilstein Journal of Organic Chemistry)
The marine sponge Suberea ianthelliformis was investigated for new chemistry after the recent discovery that polyamines ianthelliformisamines A–C (1–3) – originally sourced from this Australian sponge – act as Pseudomonas aeruginosa biofilm inhibitors and antibiotic enhancers. Large-scale extraction and isolation studies resulted in the discovery of four new and minor natural products, ianthelliformisamines D–G (4–7) and the known steroid, aplysterol (8). Compounds 4–7 were fully characterised following 1D/2D NMR, MS and UV data analyses. All compounds were assessed for their inhibition on planktonic growth of P. aeruginosa PAO1 in addition to their ability to inhibit the formation of biofilms. None of the tested natural products inhibited planktonic growth or biofilm formation of PAO1 when screened at 50 µM. Ianthelliformisamine D (4) contains a rare N-(3-aminopropyl)-2-pyrrolidone moiety only found in <30 natural products. Owing to the novelty of compound 4, we undertook the first total synthesis of this natural product, which was achieved in three steps.